Te Arawhata o Aorua, Bridging two worlds : a grounded theory study : a thesis presented in partial fulfillment of the requirements for the degree of Masters of Philosophy in Nursing at Massey University (Albany), New Zealand - Baker, Maria (Massey University, 2008)
Te Arawhata o Aorua – Bridge of two worlds is a theory about Maori mental health nurses. The aim of this study was to explore what was occurring amongst Maori mental health nurses and dual competencies. A grounded theory informed by a Maori centred research approach was adopted and conducted with three focus groups of ten Maori mental health nurses situated in one metropolitan and two provincial cities. The research design was informed by Mason Durie's Maori centred concepts of whakapiki tangata (enablement), whakatuia (integration) mana Maori (control) and integrated with grounded theory to guide the collection and analysis of the data. Audio taping and field notes were used to collect the data and the processes of constant comparative analysis, theoretical sampling and saturation were used to generate a middle range substantive Maori centred grounded theory. One core category was identified as two worlds which describes the main issue that they are grappling with. The basic social psychological process of bridging of tension explains how the two worlds are managed through two subcategories of going beyond and practising differently. Going beyond consists of two components, being Maori and enduring constant challenge that set the philosophical foundation to practice. Practising differently describes three key components as kaitiaki of wairua, it's about whanau and connecting each are blended into each other and fused into nursing practice. The impressions of the Maori mental health nurses have been interpreted and explained by this theory. The substantive grounded theory provides a model to guide health services appreciation of Maori mental health nurses, for professional development of Maori mental health nurses and to policy writers.
Keywords: Maori nurses; Mental health nurses; Nursing practice; Maori concepts; Fields of Research::320000 Medical and Health Sciences::321100 Nursing